Assessment of Dental Care and its Related Barriers in Pregnant Women of Hamadan City - Farzaneh Bayat; Akram Karimi-Shahanjarini; Saeed Bashirian; Javad Faradmal (Journal of Education and Community Health)
Background and Objectives: Oral health behaviors of pregnant women are important due to their effects on mother and child’s health. The objective of this study was to investigate dental care and its related barriers among pregnant women in Hamadan city, Iran. Materials and Methods: This cross-sectional study was carried out on 280 pregnant women in Hamadan city in 2012. We used stratified cluster sampling to select the subjects and a researcher-made questionnaire was used. The questionnaire included demographic information, common dental problems, visit of a dentist during pregnancy and tooth brushing, as well as the perceived barriers of these two behaviors. The reliability and validity of the tool were evaluated using estimates of internal consistency and the opinions of a panel of experts, respectively. Data were analyzed in SPSS-16 using logistic regression test. Results: The mean age of pregnant women was 27.2 ± 4.88 years. Tooth brushing after each meal and use of mouthwash rates were 12% and 20%, respectively. Half of the participants had not seen a dentist during their current pregnancy. The most important barriers to brush twice a day were impatience and lack of energy. Dental visit barriers were cost, low priority, and stress related to dentistry. Factors associated with no dental visit included poor economic status (P= 0.011) and working outside of home (P= 0.045). Conclusions: Given the important adverse outcomes associated with poor oral health on mothers and babies, interventions to reduce the barriers of dental cares are crucial.